Japanese consumer acceptability of commercial rice from Japan and Thailand - Sirimuangmoon, Chirat (Food and Applied Bioscience Journal, 2017)
Most rice consumed in Japan is local white rice (Japonica varieties). Many varieties of rice in global market have been introduced and eaten by consumers including aromatic, brown, and other colored types. Understanding Japanese consumer acceptability with the current varieties of rice helps rice producers and marketers to meet the consumer demands and leads to a potential for rice trading in Japan. Eight different rice samples from Japan and Thailand were evaluated by a group of 102 Japanese consumers. A sensory evaluation by asking overall degree of liking, appearance liking, flavor liking, and texture liking in each sample was conducted. Cluster analysis, internal preference mapping, and regression analysis were used to reveal the Japanese consumer acceptance. The majority of Japanese consumers liked the white rice from Japan and also Jasmine rice from Thailand. Japanese brown rice was also received a good liking score from a number of Japanese consumers. Other colored varieties including red and black varieties were not preferred by Japanese consumers. Flavor was the most important factor effecting overall degree of liking. Appearance and texture had less importance in determining overall acceptance.